Improving spectral efficiency of SAC-OCDMA systems by SPD scheme - Al-Khafaj, Hamza H.R.; Aljunid, Syed Alwee; Amphawan, Angela; Fadhil, Hilal A. (The Institute of Electronics, Information and Communication Engineers, 2012)
This letter presents a single photodiode detection (SPD) as an effective technique for eradicating both multiple-access interference (MAI) and phase-induced intensity noise (PIIN) in spectral amplitude coding optical code-division multiple-access (SAC-OCDMA) systems. Mathematical analysis and simulation experiments are used to investigate the spectral efficiency (SE) of SAC-OCDMA systems utilizing different detection techniques. Results show that the SPD technique significantly enhances the SE compared to AND as well as modified-AND subtraction detections.